2008
DOI: 10.1016/j.drugalcdep.2007.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of cannabidiol on the discriminative stimulus and place conditioning effects of Δ9-tetrahydrocannabinol

Abstract: Cannabis sativa (marijuana plant) contains myriad cannabinoid compounds; yet, investigative attention has focused almost exclusively on Δ 9 -tetrahydrocannabinol (THC), its primary psychoactive substituent. Interest in modulation of THC's effects by these other cannabinoids [e.g., cannabidiol (CBD)] has been stimulated anew by recent approval by Canada of Sativex (a 1:1 dose ratio combination of CBD:THC) for the treatment of multiple sclerosis. The goal of this study was to determine the degree to which THC's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 48 publications
7
83
2
Order By: Relevance
“…Different animal models have confirmed the low psychotropic nature of CBD [69][70][71], suggesting that in contrast to what is normally observed for THC, CBD does not have hedonic property on its own, that is, it is not rewarding and does not induce drug-seeking behavior. Such studies have demonstrated that CBD does not promote conditioned place preference [69,70] or increase the reinforcing efficacy of brain stimulation [71], which are both definitive characteristics of addictive substances.…”
Section: Cbd In Preclinical Addiction Modelsmentioning
confidence: 92%
See 1 more Smart Citation
“…Different animal models have confirmed the low psychotropic nature of CBD [69][70][71], suggesting that in contrast to what is normally observed for THC, CBD does not have hedonic property on its own, that is, it is not rewarding and does not induce drug-seeking behavior. Such studies have demonstrated that CBD does not promote conditioned place preference [69,70] or increase the reinforcing efficacy of brain stimulation [71], which are both definitive characteristics of addictive substances.…”
Section: Cbd In Preclinical Addiction Modelsmentioning
confidence: 92%
“…Findings to date suggest minimal CBD impact on apparent positive subjective effects induced by psychostimulants or THC [70,71,78]. Moreover, no animal studies have been published to date regarding CBD's effects on nicotine or alcohol.…”
Section: Cbd In Preclinical Addiction Modelsmentioning
confidence: 99%
“…Recent in vitro evidence suggests that CBD may inhibit the effects of THC through negative allosteric modulation of the CB 1 receptor, 38 whereas human neuroimaging studies indicate that THC and CBD differentially influence brain activity while performing cognitive or emotional tasks. [39][40][41] And while both additive 36 and antagonistic 18,42 associations have been reported between these agents in rodents, to date no studies have provided a direct mechanism as to how CBD moderates THC's behavioural effects.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently determined the impact of THC and CBD in isolation, as well as coadministered in ratios resembling those found in either street or medicinal cannabis. 3,5,18 Finally, we analyzed CB 1 receptor parameters ex vivo in brain regions previously implicated in effortful decision-making to determine if these were related to the behavioural effects of THC.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, CBD, when administered with THC at therapeutically relevant ratios, ameliorate aversive effects associated with initial use of THC alone (Vann et al, 2008).…”
mentioning
confidence: 99%